Semiotic analysis of presidential candidate roasting video content on TikTok’s @sandissukron - Martiyana, Devita; Ardianto, Erik (Digital Theory, Culture & Society, 2024)
This study aims to analyze the content of presidential candidate roasting videos on @sandissukron’s TikTok account using Peirce’s semiotic theory. The research method used is descriptive qualitative with data collection through indirect observation of three @sandissukron video contents and documentation studies. The results showed that the video content can be analyzed using Peirce’s semiotics, resulting in various meanings ranging from principles, traits, personalities, to implied goals. The explanation of these meanings is described in a trichotomy table consisting of sign, object, and interpretant. The gestures, intonation and coded language in the video represent the nature and personality of the intended presidential candidate. Anies Baswedan is portrayed as someone who is good at rhetoric and has a smart political strategy, Prabowo Subianto is portrayed as a power-hungry individual with a poor record on human rights, while Ganjar Pranowo is portrayed as a figure who is not trusted and is considered a party puppet. This research provides deep insight into how signs in TikTok video content can provide complex interpretations of presidential candidates and reflect public opinions and perceptions. It shows that social media has a significant role in shaping political narratives and public opinion.